1994
DOI: 10.1037/0278-6133.13.6.507
|View full text |Cite
|
Sign up to set email alerts
|

When Mom or Dad has cancer: Markers of psychological distress in cancer patients, spouses, and children.

Abstract: This study assessed anxiety/depression and stress response symptoms in adult cancer patients (n = 117), spouses (n = 76), and their children (n = 110, ages 6 to 30 years old) near the patients' diagnoses to identify family members at risk for psychological maladjustment. Patients' and family members' distress was related to appraisals of the seriousness and stressfulness of the cancer but not related to objective characteristics of the disease. Patients and spouses did not differ in anxiety/depression or in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
96
3
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(112 citation statements)
references
References 52 publications
8
96
3
5
Order By: Relevance
“…In terms of gender, female adolescents had worst physical functioning QOL and overall QOL compared to male adolescents with a parent with cancer. This finding is supported by Compas et al (1994) who reported high distress in adolescent girls whose mothers had cancer. In addition, adolescent whose mothers had cancer had significantly worst school functioning compared with adolescents whose father had cancer.…”
Section: Discussionsupporting
confidence: 79%
“…In terms of gender, female adolescents had worst physical functioning QOL and overall QOL compared to male adolescents with a parent with cancer. This finding is supported by Compas et al (1994) who reported high distress in adolescent girls whose mothers had cancer. In addition, adolescent whose mothers had cancer had significantly worst school functioning compared with adolescents whose father had cancer.…”
Section: Discussionsupporting
confidence: 79%
“…In recent years, despite the increase in the number of studies examining the psychosocial changes in those diagnosed with breast cancer, few studies investigate the effects of the disease on partners. Partners are required to support their spouses in their daily lives, to accompany them during treatments and examinations, to take greater responsibility for their home and children, all of which can lead to psychosocial problems (Given et al, 1992;Compas et al, 1994). In several studies, it was found that the partners themselves often experienced higher levels of distress than the cancer patient, and that there is a high concordance between the distress levels of the patient and the partner (Manne et al, 2004;Segrin et al, 2007;Yusoff et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that children of mothers with breast cancer exhibit a high rate of psychological and behavioural disturbance (Wellisch et al, 1992;Compas et al, 1994;Welch et al, 1996;Birenbaum et al, 1999;Nelson and While, 2002). However, Hoke (2001) found that children of breast cancer patients diagnosed during the previous year were functioning better than a sample unaffected by cancer.…”
mentioning
confidence: 99%
“…Previous research suggests that adolescent children experience most problems (Welch et al, 1996;Birenbaum et al, 1999), with teenage daughters being most at risk (Wellisch et al, 1992;Compas et al, 1994). Visser et al (2005)reported that adolescent daughters were more affected by parent's cancer treatment intensity whereas for boys it was relapse of cancer.…”
mentioning
confidence: 99%